CALCAREOUS PLANKTON HIGH RESOLUTION BIOSTRATIGRAPHY (FORAMINIFERA AND NANNOFOSSILS) OF THE UPPERMOST LANGHIAN – LOWER SERRAVALLIANRAS IL-PELLEGRIN SECTION (MALTA) - MARIA FORESI, LUCA; BONOMO, SERGIO; CARUSO, ANTONIO; DI STEFANO, ENRICO; SALVATORINI, GIANFRANCO; SPROVIERI, RODOLFO (Milano University Press, 2002)
Results of an integrated biostratigraphic (calcareous nannofossils and planktonic foraminifers) study of the uppermost Langhian/lower Serravallian Ras il-Pellegrin section (Fomm ir-Rih Bay – Malta) are presented. This high resolution study allowed us to recognise several useful lower Serravallian bio-events in the Mediterranean and to provide a detailed distribution pattern of the recognised taxa. The astrochronological calibration, reported in a different paper of this volume, provided absolute ages of the bio-events of the studied section. The LO (Last Occurrence) of Globorotalia peripheroronda at 13.39 Ma, the Paragloborotalia partimlabiata FO (First Occurrence) at 12.62 Ma and the Paragloborotalia mayeri FCO (First Common Occurrence) at 12.34 Ma among the planktonic foraminifera, and the Sphenolithus heteromorphus LO at 13.59 Ma, the Cyclicargolithus floridanus LCO (Last Common Occurrence) at 13.39 Ma, the Reticulofenestra pseudoumbilicus FCO at 13.32 Ma, the Calcidiscus macintyrei FO at 12.57 Ma and the Calcidiscus premacintyrei LCO at 12.51 Ma among the calcareous nannofossils, were recorded. Moreover, our results confirm the LO of S. heteromorphus as a fairly synchronous event in the Mediterranean and in the Atlantic and Pacific Oceans. Therefore, we suggest a lithological level near or coincident with this event for the definition of the GSSP of the Serravallian. The Ras il-Pellegrin section may be considered a good candidate for this definition.